The Effectiveness of Promotion Through Instagram and Facebook @Insta_Bumiayu on MSMEs in the South Brebes Region - Al Mubarik, Aenad; Astuti, Hernia Justiana; Innayah, Maulida Nurul; Zamakhsyari, Luthfi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effectiveness of promotions through social media Instagram and Facebook @Insta_bumiayu on promotion Micro, Small, and Medium Enterprises (MSMEs) in the South Brebes region using the EPIC Model approach which includes four dimensions: Empathy, Persuasion, Impact, and Communication. This research is a descriptive quantitative study with a sample of 100 respondents selected through a purposive sampling technique. Data were collected using an online questionnaire and analyzed through validity, reliability, and descriptive tests. The results show that all four EPIC dimensions are categorized as effective, with the Empathy dimension obtaining the highest score. The overall average value of the EPIC Rate indicates that promotions through @Insta_bumiayu are classified as effective. The promotions carried out are not only able to attract consumers' attention, but also successfully convey messages well and increase interest in MSME products. This study strengthens the role of social media as a strategic tool in supporting the growth of MSMEs in the digital era, especially through the utilization of interactive and visual features of Instagram and Facebook.